Electrospun polyacrylonitrile nanofibrous membranes supported with montmorillonite for efficient PM2.5 filtration and adsorption of Cu (II) ions. Issue 5 (1st September 2021) - Bansal, Priya; Batra, Radhika; Yadav, Reetu; Purwar, Roli
Abstract: In this study, we have fabricated polyacrylonitrile/montmorillonite (PAN/Mt) nanofibrous nanocomposites with variation in concentration of Mt from 0.25% to 1.00%. The electrospinning process developed PAN/Mt nanofibrous nanocomposites having reduced fiber diameters and high surface roughness as observed in Field emission scanning electron microscopy. The nanocomposite nanofibers were characterized by X‐ray diffraction (XRD) and thermogravimetric analyzer for intercalation and thermal stability respectively. PAN/Mt nanofibrous nanocomposites were tested for their water vapor transmission rate, air permeability, burst strength, and tensile strength. The filtration efficiency of 0.75% PAN/Mt nanofibrous nanocomposite was found to be 98.7% for PM2.5 particles present in air with a pressure drop of 46.8 Pa. The adsorption of copper (II) (Cu (II)) ions using 0.75% PAN/Mt nanofibrous nanocomposites has also been studied. The effect of contact time and initial concentration of adsorbent on the adsorption of Cu (II) ions have been analyzed. It was found that the PAN/Mt nanofibrous membranes follows pseudo‐second‐order kinetic model and Langmuir adsorption isotherm for the adsorption of Cu (II) ions from aqueous solutions. This study suggests the potential implication of PAN/Mt nanofibrous nanocomposites for filtration of PM2.5 and adsorption of metal ions. Abstract : Electrospun polyacrylonitrile nanofibrous membranes have been developed by addition of montmorillonite with varying concentrations from 0.25% to 1.00%. The addition of Mt to PAN nanofibrous membranes enhanced the thermal stability and reduced pressure drop to 46.8 Pa cm −2 . The maximum Cu (II) adsorption amount using PAN/ Mt nanofibrous membranes was found to be 227.27 mg g −1 .